2017
DOI: 10.3168/jds.2016-12221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prepartum dietary cation-anion difference on aspects of peripartum mineral and energy metabolism and performance of multiparous Holstein cows

Abstract: The objectives of this study were to determine the effect of decreasing dietary cation-anion difference [DCAD; (Na + K) - (Cl + S)] of the prepartum diet on aspects of mineral metabolism, energy metabolism, and performance of peripartum dairy cows. Multiparous Holstein cows (n = 89) were enrolled between 38 and 31 d before expected parturition and randomized to treatments in a completely randomized design (restricted to balance for previous 305-d mature equivalent milk production, parity, and body condition sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 56 publications
10
54
7
Order By: Relevance
“…The target study population was 50 cows and we assumed that 10 cows would be removed because of twinning or for health reasons. The sample size determination was based on biologically important differences in serum Ca concentrations between parturition and 2 DIM from previous work done by Leno et al (2017). The detectable difference in Ca concentration between the 2 treatments was at least 0.20 mmol/L, with α = 0.05 and β = 0.20.…”
Section: Study Population Experimental Design and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The target study population was 50 cows and we assumed that 10 cows would be removed because of twinning or for health reasons. The sample size determination was based on biologically important differences in serum Ca concentrations between parturition and 2 DIM from previous work done by Leno et al (2017). The detectable difference in Ca concentration between the 2 treatments was at least 0.20 mmol/L, with α = 0.05 and β = 0.20.…”
Section: Study Population Experimental Design and Treatmentsmentioning
confidence: 99%
“…Samples of TMR were then composited at 4-wk intervals and feed ingredients were composited over the course of the study. Composited samples were submitted to a commercial laboratory (Cumberland Valley Analytical Services, Waynesboro, PA) for wet chemistry analysis as described by Leno et al (2017). Results from analysis of composited forage samples were input into CNCPS v. 6.5 to determine predicted dietary MP concentrations.…”
Section: Diet Formulation and Feeding Managementmentioning
confidence: 99%
“…Metabolic acidosis level prepartum can be easily monitored by measuring either urinary calcium concentrations or urinary pH (Martin-Tereso and Martens, 2014). As described by Leno et al (2017) cows fed a negative DCAD diet prepartum (−74 mEq/kg DM) increased urinary calcium excretion (8.2 v. 0.7 g/ day, in negative DCAD diet and control cows, respectively) and maintained urine pH between 5.5 and 6.0 compared to the control cows (urine pH 7.89). Additionally, circulating calcium concentrations (2.27 v. 2.16 mmol/l), feed intake (3.07% v. 2.88% of BW) and milk yield (43.9 v. 40.8 kg/day) increased postpartum in cows fed a negative DCAD diet compared to control cows.…”
Section: Traditional Management Practices For the Prevention Of Hypocmentioning
confidence: 57%
“…Urine pH is a useful indicator to monitor the effect of a reduced DCAD diet on acid-base balance in goats and sheep [71,72], dairy cows [8,73,74], and buffalo [4]. This phenomenon can be explained using the strong ion difference theory of Stewart [75], who argued that with reductions of DCAD, the concentration of anions in blood would increase and cause the kidney to expel redundant H + in urine, resulting in lower urine pH.…”
Section: Discussionmentioning
confidence: 99%
“…The DCAD level has been an important parameter in the process of formulating diets in recent years [3][4][5][6][7]. Studies have shown that diets with a lower DCAD could enhance the health and extend the economic life of transition mammary animals [8][9][10].…”
Section: Introductionmentioning
confidence: 99%